Enhanced Raman and photoluminescence response in monolayer MoS2 due to laser healing of defects. (27th July 2017) - Bera, Achintya; Muthu, D. V. S.; Sood, A. K.
Abstract : Bound quasiparticles, negatively charged trions and neutral excitons are associated with the direct optical transitions at the K‐points of the Brillouin zone for monolayer MoS2 . The change in the carrier concentration, surrounding dielectric constant, and defect concentration can modulate the photoluminescence and Raman spectra. Here, we show that exposing the monolayer MoS2 in air to a modest laser intensity for a brief period of time enhances simultaneously the photoluminescence intensity associated with both trions and excitons, together with ∼3 to 5 times increase of the Raman intensity of first‐order and second‐order modes. The simultaneous increase of photoluminescence from trions and excitons cannot be understood based only on known scenario of depletion of electron concentration in MoS2 by adsorption of O2 and H2 O molecules. This is explained by laser‐induced healing of defect states resulting in reduction of nonradiative Auger processes. This laser healing is corroborated by an observed increase of intensity of both the first‐order and second‐order longitudinal acoustic Raman modes at the M‐point of Brillouin zone by a factor of ∼3 to 5. The A 1g mode hardens by ∼1.4 cm −1, whereas the E 2 g 1 mode softens by ∼1 cm −1 . The second‐order longitudinal acoustic Raman mode at the M‐point of Brillouin zone at ∼440 cm −1 shows an increase in wavenumber by ∼8 cm −1 with laser exposure. These changes are a combined effect of change in electron concentrations and oxygen‐induced lattice displacements. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We show that a modest exposure of monolayer MoS2 in air to laser irradiation results in simultaneous enhancement of the photoluminescence (PL) associated with both trions and excitons as well as Raman intensity of the Raman modes. The simultaneous increase of trion and exciton PL is shown to be possible only due to laser‐assisted passivation of S vacancies by oxygen. The observed changes in PL and Raman data are explained in terms of combined effects of change in electron concentrations and oxygen‐induced lattice displacements.